Coordinator perceptions when assessing the impact of citizen science towards sustainable development goals - Sprinks, James; Woods, Sasha Marie; Parkinson, Stephen; Wehn, Uta; Joyce, Hannah; Ceccaroni, Luigi; Gharesifard, Mohammad (MDPI, 2021)
Tracking progress towards the United Nations’ Sustainable Development Goals (SDGs) requires high-quality, timely, and accessible data, often in areas where data are rarely available. Problems exist due to socioeconomic variations between countries and the qualitative nature of certain indicators in their definition. Citizen science has the potential to contribute to several SDGs. However, whilst citizen science’s potential to contribute towards SDGs is well documented, limitations exist when measuring the impact that citizen science has made toward SDG progress. To better understand the issues and prospective solutions surrounding impact assessment towards SDG progress, this work presents the outcomes of semi-structured interviews with citizen science project coordinators. They reveal the complex nature of impact assessment within a citizen science context. Coordinators demonstrate greater confidence when the project is easier to relate to the SDGs, and the project methodology can objectively measure indicators. Issues exist, however, when considering SDGs with a broader, global context, those more difficult to link to project goals and when the project’s impact on them happens at timescales beyond the funding period. If the full potential of citizen-science contributions to the SDGs is to be realised, approaches are needed to fully consider practitioners’ needs and motivations.
Keywords: citizen science; Sustainable Development Goals; semi-structured interviews; impact assessment